NILAI-NILAI LUHUR DALAM AL-QUR’AN DAN KEARIFAN LOKAL BUGIS SEBAGAI LANDASAN MEMBANGUN GOOD GOVERNANCE DI INDONESIA - Muhammad Yusuf (Sekolah Tinggi Agama Islam (STAI) Sadra, 2017)
This paper discloses the view concerning the urgency of values of Islamic teaching and values of local wisdom of Bugis people in constructing the system of good governance in Indonesia. Based on what al-Qur’an has insisted that the positive and effective change must be begun from the inner side of awarness and should be done collectively whether in the structural or cultural basis. Inner change encompasses two elements, mindset and knowledge, in such a way the internalization of glorious values from the al-Qur’anic teaching must be done in the self of each indivual and, furthermore, enable to make good social life and good governance as well. This kind of internalization of glorious values also showed in local wisdom of Bugis which is implied in the concept of “ade’”. Acoording to Bugis people, ade’ is an essence of human being, since it is a reason why a man is named as human being. For Bugis people, ade’ is a value. The ethical codes and values are called pangngadereng. There is a number of Local wisdom and values in the ethnic of Bugis, namely: lempu’, amaccang, agettengeng, asitinajang, and reso which must be internalized and applied in this life then, in further way, have direct implication for good social life and also for good governance. By means of comparative-descriptive method, this paper attempts to portrait these two points of view and hopefully it can show the conformity between them with respect to glorious values and wisdom.